Association between Frailty and Depression among Elderly in Nursing Home - Darwis, Zuhal; Safei, Imran (Surabaya Physical Medicine and Rehabilitation Journal, 2022)
Background: Frailty is described by the collective decline of multiple physiological systems and increased vulnerability to multiple stressors. It is also linked to emotional distress and mental illness, especially depression. Both frailty and depression are correlated with many harmful consequences in the elderly, including decreased quality of life, escalated utilization of health services, and elevated morbidity and mortality. Given the prominence of frailty and depression in the elderly, and the deleterious consequences when they coexist, understanding the association between these factors is essential. Aim: This study aims to analyze the association between frailty and depression among the elderly in the nursing home. Material and Methods: This research was cross-sectional, and conducted at 3 nursing homes in South Sulawesi. Frailty and depression were measured. Frailty was assessed by Edmonton Frail Scale (EFS), while depression was evaluated by Geriatric Depression Scale (GDS). The data were analyzed with the Pearson test in SPSS 25. Results: There were 27 participants, consisting of females 19 (70.3%), and males 8 (29.6%) with a mean age was 73.15±8, included in this study. The mean EFS was 5.89±3.15. The mean GDS result was 3.74±3.14. Frailty has positive strong association with depression (r=0.6, p=0.001). Conclusion: There was a strong and substantial association between frailty and depression among the elderly in the nursing home.